Roles of Long Noncoding RNAs in Conferring Glioma Progression and Treatment - Qin, Jie; Jiang, Chuanlu; Cai, Jinquan; Meng, Xiangqi (Frontiers in Oncology, 2021)
Accompanying the development in biomedicine, the insight of glioma, one of the most common primary intracranial carcinomas, is getting more comprehensive. Unfortunately, patients with glioblastoma (GBM) still have dismal prognosis and high relapse rate, even though undergoing standard combination therapy, namely surgical resection, postoperative radiotherapy and chemotherapy. The absence of validated biomarkers is responsible for the majority of such terrible outcomes, and reliable therapeutic targets are indispensable for improving the prognosis of patients suffering from gliomas. Exploring both precise diagnostic and accurate prognostic markers and promising therapeutic targets has therefore attracted considerable attention from researchers. Encouragingly, accumulating evidence has demonstrated that long non-coding RNAs (lncRNAs) perform significant roles in the pathogenesis and oncogenesis of various categories of human tumors, including gliomas. Nevertheless, the underlying mechanisms by which lncRNAs regulate diverse biological behaviors of glioma cells, such as proliferation, invasion and migration, remain poorly comprehended. Consequently, this review builds on previous studies to further summarize the progress in the field of lncRNAs regulation of gliomas over recent years and addresses the potential of lncRNAs as diagnostic and prognostic markers and therapeutic targets.